Identification of mitophagy-related genes in patients with acute myocardial infarction - Ju-Ying Li; Hong-Kui Chen; Yi-Hao Huang; Yu-Peng Zhi; Yue-E Li; Kai-Yang Lin; Chun Chen; Yan-Song Guo (Hereditas)
Abstract Mitophagy is involved in acute myocardial infarction (AMI) process. However, the role of mitophagy-related genes (MRGs) in the AMI process is not well illustrated. We identified MRGs involved in AMI by bioinformatics analysis. The external datasets were employed for the validation of the MRGs, alongside the execution of cellular and animal experiments. Forty-five MRGs were detected, and machine learning identified the top four hub genes, namely ALDH2, ACSL1, IL1B, and GABARAPL1. Additionally, an external validation set was used to screen for three diagnostic markers (ACSL1, IL1B, and GABARAPL1) among these hub genes. Immune infiltration analysis revealed changes in the immune microenvironment among patients with AMI. Finally, the significant upregulation of ACSL1, IL1B, and GABARAPL1 in both cellular and animal models was confirmed. The occurrence of mitophagy was observed in the cell model through transmission electron microscopy (TEM). Our study demonstrated that ACSL1, IL1B, and GABARAPL1 possess potential biomarkers for AMI.